2019
DOI: 10.1186/s12961-019-0440-3
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Australian policy-makers on the potential benefits and risks of technologically enhanced communicable disease surveillance – a modified Delphi survey

Abstract: Background Event-based social media monitoring and pathogen whole genome sequencing (WGS) will enhance communicable disease surveillance research and systems. If linked electronically and scanned systematically, the information provided by these technologies could be mined to uncover new epidemiological patterns and associations much faster than traditional public health approaches. The benefits of earlier outbreak detection are significant, but implementation could be opposed in the absence of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…The same requirement could have been expected for data quality of any surveillance system, considering the importance placed on it by Australian practitioners and policymakers, in expert and public discourses. 23 28 The decline in importance given to data certainty/confidence by respondents after COVID-19 outbreak onset suggests that its operational value might not have been widely appreciated at the time of data collection. In real-world systems, data accuracy, utility and privacy are competing attributes—such that a lack of data accuracy can either wrongly identify an individual as being affected, if data specificity is poor, or fail to detect another if sensitivity is lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The same requirement could have been expected for data quality of any surveillance system, considering the importance placed on it by Australian practitioners and policymakers, in expert and public discourses. 23 28 The decline in importance given to data certainty/confidence by respondents after COVID-19 outbreak onset suggests that its operational value might not have been widely appreciated at the time of data collection. In real-world systems, data accuracy, utility and privacy are competing attributes—such that a lack of data accuracy can either wrongly identify an individual as being affected, if data specificity is poor, or fail to detect another if sensitivity is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified that public acceptability was a key consideration for Australian practitioners and policymakers, in deciding how and when to use technologies to enhance communicable disease surveillance systems. 23 Unless the threat to public health was imminent, the potential for such systems to erode public trust was seen as a crucial barrier to implementation, whereby the development of publicly supported guidelines and systems of oversight was identified as a necessary condition for their operation. Therefore, the extent to which preferred surveillance system attributes remained stable between the two data collection periods is notable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on the outcomes of a preparatory Delphi process [49], we consulted a dozen relevant Australian policymakers and public health practitioners (including several State/Territory Chief Health Officers, directors of communicable disease branches and public health laboratories which employ WGS based surveillance of communicable diseases) to design the questions for the juries' consideration ( Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Decisions, about what data should be collected and what action thresholds are used, are not just matters for experts [37]. To secure social licence, these systems must align with community values; this can be facilitated by structured public dialogue to develop ethically and legally defensible justification for their design and operation [6,49]. In this paper, we report on four community juries convened to consider the acceptability and legitimacy of using new technologies to enhance public health research and communicable disease surveillance.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%